2018
DOI: 10.1016/j.sdentj.2018.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Total and soluble fluoride concentration present in various commercial brands of children toothpastes available in Saudi Arabia – A pilot study

Abstract: The analysis of TF and TSF concentrations revealed variations from the labelled claims. Therefore, some of the toothpastes may have doubtful anti-caries effectiveness owing to deficiency of total and soluble fluoride.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Benzain H et al (2012) had analysed 115 samples and stated that the 85% of the children toothpastes had less total flouride concentration than that claimed on the label, similar to sample H in our study [19]. Farooq I et al (2018) he analysed three samples of five different commercial brands of children toothpastes for its total fluoride concentration and total soluble fluoride concentration. The measured total flouride in 2 toothpastes was higher than mentioned, which is similar to sample H in this study while 3 were lower than mentioned on label which is similar to sample G in this study [20].…”
Section: Resultssupporting
confidence: 69%
“…Benzain H et al (2012) had analysed 115 samples and stated that the 85% of the children toothpastes had less total flouride concentration than that claimed on the label, similar to sample H in our study [19]. Farooq I et al (2018) he analysed three samples of five different commercial brands of children toothpastes for its total fluoride concentration and total soluble fluoride concentration. The measured total flouride in 2 toothpastes was higher than mentioned, which is similar to sample H in this study while 3 were lower than mentioned on label which is similar to sample G in this study [20].…”
Section: Resultssupporting
confidence: 69%
“…However, during toothpaste storage, hydrolyzed releasing of F's ion from MFP reacts with Ca++ from the abrasive, forming insoluble and inactive F salts. Thus, the concentration of soluble F during storage could be lower than the minimum to impair the anti‐caries effects of some formulations 11,13,16–19 . Studies have been developed to observe the F concentration and stability of toothpastes and they have confirmed that before expiration dates, toothpastes may not be able to maintain the minimum concentration required to yield maximum anti‐caries effect 7,11,13,15–17 …”
Section: Introductionmentioning
confidence: 99%
“…Thus, the concentration of soluble F during storage could be lower than the minimum to impair the anti-caries effects of some formulations. 11,13,[16][17][18][19] Studies have been developed to observe the F concentration and stability of toothpastes and they have confirmed that before expiration dates, toothpastes may not be able to maintain the minimum concentration required to yield maximum anti-caries effect. 7,11,13,[15][16][17] Sometimes, the toothpaste's expiration date has nothing to do with the amount of total soluble fluoride (TSF).…”
mentioning
confidence: 99%
“…International studies that have compiled lists of children’s toothpastes available to purchase have found that almost all toothpastes available were fluoridated 12–15 . However, there is no known literature containing an audited list of toothpastes available on the Australian market.…”
Section: Introductionmentioning
confidence: 99%